The Impact of In-Work Benefits on Poverty and Household Labour Supply A Simulation Study for Switzerland - Michael Gerfin; Robert E. Leu (Institute for the Study of Labor (IZA), 2003)
Income support for working low income families (the ?working poor?) is on top of the political agenda in Switzerland. The current social assistance system is considered inadequate to support working poor households. Labour unions propose the introduction of a general minimum wage, whereas the Swiss government promotes in-work benefits. Based on a structural labour supply model this paper provides microsimulation results of the effects of introducing different schemes of in-work benefits. It turns out that adding a minimum hours requirement to the current social assistance system is the most cost-efficient reform. Minimum wages are ineffective in fighting poverty.
Keywords: I38; C25; J22; 330; tax credits; household labour supply; microsimulation; poverty; Lohnsubvention; Negative Einkommensteuer; Wirtschaftspolitische Wirkungsanalyse; Niedrigeinkommen; Arbeitsangebot; Armut; Theorie; Schweiz